Penerapan Teori Van Hiele pada Materi Volume Bangun Ruang Kelas IV di SDIT Luqmanul Hakim - Husna, Raudatul; Yusaini, Yusaini; Azhari, Intan (Al-Azkiya: Jurnal Pendidikan MI/SD, 2024)
This research addresses the lack of student enthusiasm for mathematics and the low learning outcomes of fourth-grade students at SDIT Lukmanul Hakim regarding cubes and rectangular prisms. To tackle this issue, the Van Hiele theory is applied, which includes five stages of learning: information, orientation, and explicitness. The study investigates how a learning model based on the Van Hiele theory affects the students' understanding of these concepts. Conducted as classroom action research (CAR) in 2 cycles, the study involved 27 students of class 4B at SDIT Lukmanul Hakim. Data were collected through observations, interviews, tests, and documentation. Results showed that in Cycle I, only 62.96% of students achieved the competency indicators due to challenges in motivation and enthusiasm. However, in Cycle II, 85% of students achieved learning mastery. Thus, the application of the Van Hiele theory positively influences student learning outcomes.